2006
DOI: 10.1128/aem.72.3.2070-2079.2006
|View full text |Cite
|
Sign up to set email alerts
|

The atu and liu Clusters Are Involved in the Catabolic Pathways for Acyclic Monoterpenes and Leucine in Pseudomonas aeruginosa

Abstract: , an enzyme with bifunctional activity that is essential for both AMTC and leucine degradation. P. aeruginosa PAO1 products encoded by the liuABCD cluster showed a higher sequence similarity (77.2 to 79.5%) with the probable products of liu clusters from several Pseudomonas species than with the atuCDEF cluster from PAO1 (41.5%). Phylogenetic studies suggest that the atu cluster from P. aeruginosa could be the result of horizontal transfer from Alphaproteobacteria. Our results suggest that the atu and liu clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 35 publications
7
68
0
Order By: Relevance
“…As can be observed in Figure 3, metabolites accumulated during citronellal, citronellol and citronellyl acetate degradation, particularly citronellic and geranic acids, are in accordance with those previously reported on P. aeruginosa and P. citronellolis (Díaz-Pérez et al 2004;Aguilar et al 2006;Föster-Fromme et al 2006), indicating that P. mendocina uses the general citronellol catabolic pathway described for these bacteria. Citronellol in citronellal control sample ( Figure 3IA), as well as dimethyl octanol and dimethyl octadienol ( Figure 3IB), were contaminants of the practical grade citronellal (93% purity) used in media preparation.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…As can be observed in Figure 3, metabolites accumulated during citronellal, citronellol and citronellyl acetate degradation, particularly citronellic and geranic acids, are in accordance with those previously reported on P. aeruginosa and P. citronellolis (Díaz-Pérez et al 2004;Aguilar et al 2006;Föster-Fromme et al 2006), indicating that P. mendocina uses the general citronellol catabolic pathway described for these bacteria. Citronellol in citronellal control sample ( Figure 3IA), as well as dimethyl octanol and dimethyl octadienol ( Figure 3IB), were contaminants of the practical grade citronellal (93% purity) used in media preparation.…”
Section: Resultssupporting
confidence: 79%
“…Although both are acyclic monoterpenes, the degradation of citronellol and myrcene is achieved by different catabolic pathways with specific genes and enzymes (Iurescia et al 1999;Aguilar et al 2006;Föster-Fromme et al 2006). Conversely, the citronellol and geraniol degradation pathways share most of the enzymes, and the ability of IBPse 105 to use just one of these monoterpenes, confirms the existence of different metabolic routes (upper pathway) for their oxidation .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The most information on biochemical pathways of acyclic terpenes in aerobes exists for P. aeruginosa and P. citronellolis: in our previous studies we identified the atuRABCDEFGH gene cluster of P. aeruginosa (Förster-Fromme et al, 2006;Höschle et al, 2005) and a highly similar atuRABCDEFGH gene cluster in P. citronellolis (Förster-Fromme & Jendrossek, 2006) that were essential for acyclic terpene utilization (Atu) in both species. atuC and atuF were identified to encode the two subunits of the key enzyme of the Atu pathway, geranyl-CoA carboxylase (Aguilar et al, 2006;Höschle et al, 2005). It is assumed that the atu gene cluster codes for proteins catalysing the conversion of acyclic terpenes such as citronellol into 7-methyl-3-oxo-6-octenoyl-CoA (Fig.…”
Section: Introductionmentioning
confidence: 99%